Edukasi Terapi Non Farmakologi Kompres Dingin pada Masyarakat Dengan Low Back Pain - Lana One, Vinsensius; Susanto, Amin; Haniyah, Siti (Yayasan Inspirasi El Burhani, 2025)
Introduction: Low Back Pain (LBP) is one of the most common musculoskeletal problems, especially in the elderly. The causes of LBP include incorrect posture, lack of physical activity, and structural abnormalities of the spine. One effective and safe alternative to LBP treatment is non-pharmacological therapy in the form of cold packs, which work to reduce inflammation and draw pain impulses to sensory nerves. Objective: This activity aims to increase participants' knowledge about cold compress therapy in reducing low back pain. Method: The method used was direct education to 30 participants at Posyandu RW 5 Ledug, with measurement of knowledge level through pre-test and post-test. Education was delivered using leaflet media and demonstration of proper cold compress techniques. Result: The results of the activity showed a significant increase in knowledge. Before the education, only 10% of participants had good knowledge, and after the education, it increased to 80%. The majority of the elderly involved were over 60 years old and had a basic education level, but still showed enthusiasm and a good understanding of the material. Conclusion: The conclusion of this study is that cold compress therapy education is proven effective in increasing participants' knowledge about LBP management. This therapy can be a self-intervention that is easy to implement, safe, and efficient in community health services, especially for elderly groups who are prone to low back pain.